2014
DOI: 10.1007/s11120-014-0042-4
|View full text |Cite
|
Sign up to set email alerts
|

Photophysiology and daily primary production of a temperate symbiotic gorgonian

Abstract: Gorgonians are one of the most important benthic components of tropical and temperate areas, and play a fundamental role as ecosystem engineers. Although global warming and pollution increasingly threaten them, the acquisition of nutrients, which is a key process in fitness and stress resistance, has been poorly investigated in such species. This study has thus used an advanced in situ incubation chamber for the first time with gorgonians, to assess the daily acquisition of nutrients and the photophysiology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…A P:R > 1 indicates that the holobiont acquires more photosynthetic organic material than it consumes and can therefore rely on autotrophy for its energetic needs. The first few studies which have assessed the rates of photosynthesis and respiration of zooxanthellate octocorals measured very low rates of primary productivity compared to scleractinian corals, both in the temperate [ 44 ] and tropical [ 7 , 45 ] areas. It was also observed that the presence of Symbiodinium increased metabolic costs, and thereby respiration rates [ 46 ], indeed suggesting that these octocorals have to rely on both auto-and heterotrophy to sustain their metabolic needs.…”
Section: The Algal Symbiont Symbiodiniummentioning
confidence: 99%
See 1 more Smart Citation
“…A P:R > 1 indicates that the holobiont acquires more photosynthetic organic material than it consumes and can therefore rely on autotrophy for its energetic needs. The first few studies which have assessed the rates of photosynthesis and respiration of zooxanthellate octocorals measured very low rates of primary productivity compared to scleractinian corals, both in the temperate [ 44 ] and tropical [ 7 , 45 ] areas. It was also observed that the presence of Symbiodinium increased metabolic costs, and thereby respiration rates [ 46 ], indeed suggesting that these octocorals have to rely on both auto-and heterotrophy to sustain their metabolic needs.…”
Section: The Algal Symbiont Symbiodiniummentioning
confidence: 99%
“…Subsequent studies, performed on a greater number of species, however, showed that octocoral primary productivity depends on the environment, the polyp activity, the Symbiodinium clade identity, and the host morphology. For example, the P:R ratio tends to be the lowest in summer for tropical species (due to photoinhibition of the symbionts’ activity) [ 47 ], while it is the highest in summer for temperate areas, which are light limited during the other seasons [ 44 , 48 , 49 ]. For the same environment, the P:R ratio is also linked to the surface area:volume ratio (SA:V ratio).…”
Section: The Algal Symbiont Symbiodiniummentioning
confidence: 99%
“…11 Trade-off between polyp size and feeding effectiveness over a range of flow velocities (Adapted from Dai and Lin 1993) Fig. 12 Comparison of respiratory rates of symbiotic (dark yellow) and nonsymbiotic species (dark red) from the Great Barrier Reef (Fabricius and Klumpp 1995), the Red Sea (Svoboda 1978;, and the Mediterranean (Brafield and Chapman 1965;Coma et al 1998;Ribes et al 2003;Previati et al 2010;Ferrier-Pagès et al 2015). Numbers of species included are given in parentheses Fig.…”
Section: Polyp Feeding Effectiveness (Polyp -1 )mentioning
confidence: 99%
“…Except in early spring, feeding on zooplankton and seston in general has a low contribution to the respiratory demands of this species (Previati et al 2010). Therefore, to meet basal metabolic requirements, this species depends on autotrophic input through symbiont photosynthesis, which has been shown to fulfill E. singularis respiratory demands during summer (Ezzat et al 2013;Ferrier-Pagès et al 2015). In contrast, the temperate Capnella gabonensis relies very little on carbon transfer from symbionts (translocation of approximately 10% of photosynthates; Farrant et al 1987) and uses heterotrophic input to fulfill its energy demands.…”
Section: Polyp Feeding Effectiveness (Polyp -1 )mentioning
confidence: 99%
See 1 more Smart Citation